2017
DOI: 10.15804/tner.2017.47.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Influence of School Factors on Students’ Sense of School Belonging

Abstract: Sense of school belonging is related to school/classroom social membership. Students' sense of school belonging depends on teachers, classmates and parents, and arises from a positive interpersonal relationship based on care and support, which contributes to students' sense of community. Th e scientifi c problem analysed in the article is defi ned by the following question: which factors of school educational environment are signifi cant for the sense of school belonging and social membership to arise? Th e da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
3
0
3
Order By: Relevance
“…Recent studies suggested that one of the most important determinants of school belonging is the quality of the relationship students develop with their teacher (Ahmadi et al, 2020;Dukynaitė & Dudaitė, 2017;St-Amand, 2018;St-Amand et al, 2017a). One way to develop healthy relations is the teacher's ability to implement and apply classroom rules to foster a climate conducive to learning (Emmer & Sabornie, 2015) and avoid fostering a climate of injustice (Janosz et al, 1998).…”
Section: Theoretical Perspective Of This Studymentioning
confidence: 99%
“…Recent studies suggested that one of the most important determinants of school belonging is the quality of the relationship students develop with their teacher (Ahmadi et al, 2020;Dukynaitė & Dudaitė, 2017;St-Amand, 2018;St-Amand et al, 2017a). One way to develop healthy relations is the teacher's ability to implement and apply classroom rules to foster a climate conducive to learning (Emmer & Sabornie, 2015) and avoid fostering a climate of injustice (Janosz et al, 1998).…”
Section: Theoretical Perspective Of This Studymentioning
confidence: 99%
“…У зв'язку з цим зростає роль навчального закладу в охороні та зміцнені здоров'я дітей та підлітків [13,14]. Гігієнічна оцінка освітнього середовища та впливу його чинників на стан здоров'я учнів є основою здоров'язберігаючої діяльності сучасної школи [15,16]. Проблеми формування здоров'язберігаючої поведінки відзначені у роботах В. Бобрицької, Ю. Бойчука, О. Дубогай, Р. Карпюка, С. Омельченко та ін.…”
Section: вступunclassified
“…As an emotional and psychological construct, university students' sense of SB reflects their positive attachment to the collegiate community and their culturally and academically transitional adaptation to a new surrounding [6][7][8]. Scholars have identified crucial predictors of SB in university settings that can be categorized into positive and negative facets [9,10]. Regarding the positive factors, the culturally relevant antecedents (e.g., cultural intelligence, CI) have been significantly linked to enhancing the sense of SB among the university population [11,12].…”
Section: Introductionmentioning
confidence: 99%